2020
DOI: 10.3390/jcm9123797
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sport Participation and Age at Menarche in Relation to Midlife Body Composition, Bone Mineral Density, Fitness, and Physical Activity

Abstract: This study aimed to investigate the associations of competitive sport participation in adolescence and age at menarche (AAM) with body composition, femoral neck bone mineral density (BMD), physical performance, and physical activity (PA) in middle-aged women. 1098 women aged 47–55 years formed the sample of this retrospective study. Participants self-reported their PA level at age 13–16 years and AAM. The protocol also included dual-energy X-ray absorptiometry, physical performance tests, and accelerometer-mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 102 publications
(136 reference statements)
2
24
1
Order By: Relevance
“…(6)(7)(8)14,15) A high level of PA in childhood is also associated with high peak bone mass (6)(7)(8) and low fracture incidence in adulthood. (16)(17)(18)(19)(20)(21) This is reasonable, as 50% of the variance in bone mass in old age is predicted by peak bone mass (22) and a 10% increase in peak bone mass delays osteoporosis by 13 years. (23) Others question this view, reporting that PA-induced high bone mass is attenuated if the level of activity is reduced.…”
Section: Introductionmentioning
confidence: 82%
“…(6)(7)(8)14,15) A high level of PA in childhood is also associated with high peak bone mass (6)(7)(8) and low fracture incidence in adulthood. (16)(17)(18)(19)(20)(21) This is reasonable, as 50% of the variance in bone mass in old age is predicted by peak bone mass (22) and a 10% increase in peak bone mass delays osteoporosis by 13 years. (23) Others question this view, reporting that PA-induced high bone mass is attenuated if the level of activity is reduced.…”
Section: Introductionmentioning
confidence: 82%
“…Some studies infer that reduced level of PA is followed by greater loss in bone mass than expected with age [ 16 , 21 , 22 ]. Others oppose this view, with reports indicating that exercise-induced bone mass benefits in young years are retained in adulthood [ 12 16 , 23 , 24 ], and that children with a high level of PA during growth have a lower fracture incidence in adulthood [ 12 , 13 , 15 , 16 ]. These studies, however, included individuals with a self-selected high level of PA, who already at baseline had high bone mass and superior muscle function [ 12 16 , 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies infer that a cessation of high level of PA is followed by greater loss in bone mass than expected by age [ 16 , 21 , 22 ]. Others, however, found that bone mass benefits are retained [ 12 16 , 23 , 24 ]. Due to the conflicting results, there is a need for longitudinal controlled studies that follow individuals from before PA intervention, during the period with PA intervention and after the termination of PA intervention.…”
Section: Introductionmentioning
confidence: 99%
“…(10,11) Peak bone mass is further estimated to predict 50% of the variance in bone mass at old age, (12) and a 10% increase in peak bone mass delays the development of osteoporosis by 13 years. (13) It is therefore possible that increased physical activity, initiated before or in early puberty, could counteract osteoporosis (10,11) and decrease fracture risk in adulthood. (3,7,10,11) Despite the above knowledge, physical inactivity has reached enormous proportions.…”
Section: Introductionmentioning
confidence: 99%
“…(13) It is therefore possible that increased physical activity, initiated before or in early puberty, could counteract osteoporosis (10,11) and decrease fracture risk in adulthood. (3,7,10,11) Despite the above knowledge, physical inactivity has reached enormous proportions. (14,15) This type of inactivity may continue further as screen time activity through computers, tablets, and smart phones is increasing, (14) nowadays covering as much as 40% to 60% of all sitting time for children.…”
Section: Introductionmentioning
confidence: 99%